BAHAN AJAR MENYAJIKAN TEKS PERSUASIF DENGAN MEDIA GAMBAR BERSERI UNTUK SISWA KELAS VIII SMP/MTS - Ika Nurmalia Indah; Eli Herlina; Saroni Saroni (Universitas Wiralodra, 2023)
This research is motivated by the problem of teaching materials used by teachers and students. So far, persuasive text teaching materials used in class VIII SMP/MTs are still very limited. The learning process with a lack of appropriate techniques and media is one of the factors in learning persuasive texts that are less attractive and difficult. The formulation of the problem in this study is formulated as follows. (1) How do the teaching materials present persuasive texts with serial picture media for Grade VIII students of SMP/MTs?; (2) Are teaching materials presenting persuasive texts using serialized images media appropriate to be used as alternative teaching materials for class VIII students of SMP/MTs?; (3) How is the student's response to teaching materials presenting persuasive texts with serial picture media for Grade VIII students of SMP/MTs? The purpose of this research is to know and describe: (1). teaching materials presenting persuasive texts with serial picture media for class VIII students of SMP/MTs; (2) the feasibility of teaching materials in presenting persuasive texts with serial picture media for class VIII students of SMP/MTs; (3) student responses to teaching materials presenting persuasive texts with serial picture media for class VIII students of SMP/MTs. The method used in this research is descriptive method with a qualitative approach. The data sources for this study were respondents, namely two Indonesian language teachers as validators and five students of class VIII SMP. Meanwhile, the data in this study were from previous research, reference books, and similar research journals. The techniques used are interview techniques and questionnaires or questionnaires. Based on the results of the study it can be concluded as follows. (1) The teaching materials are arranged in a systematic and structured manner in accordance with KD in the 2013 Curriculum. The teaching materials present persuasive texts with serial picture media including instructions for using modules, concept maps, core competencies, student worksheets and answer key sheets. Teaching materials presenting persuasive texts have two learning activities, namely examining the structure and language rules of persuasive texts and presenting persuasive texts. (2) The results of the combined validation between material experts and media experts obtained an average value of 86.50%. This value indicates that teaching materials presenting persuasive text with serial image media are very valid and appropriate to use. (3) The results of student responses or responses as a whole to teaching materials, obtained an average value of 87.5. This value indicates that the five students responded very well to teaching materials presenting persuasive texts using serial picture media.